Contribution of particle morphology on flotation and aggregation of sphalerite particles. (1st May 2021) - Uysal, T.; Guven, O.; Ozdemir, O.; Karaagaclioglu, İ.E. and Tunç, B. and Çelik, M.S.
Highlights: Rounder and rougher sphalerite particles lead to an increase in flotation recoveries. Roundness factor increased the flotation recovery and aggregation up to 1.5 and 1.2 times. Roughness factor also increased the flotation recovery and aggregation up to 2.8 and 3.1 times. Abstract: Physical properties such as particle morphology (shape and roughness) play an important role in the flotation process to understand the bubble-particle and particle–particle interactions. In this study, a new approach was suggested for the first time to correlate the aggregation and flotation of sphalerite mineral along with the contribution of morphological variations. Towards this aim, fine particles of −74 + 38 μm were produced with a ball mill while the effect of grinding time was investigated on morphology. In addition to the grinding, the roughness of particles was tuned through an abrasion treatment with silicon carbide. The shape factor of particles determined by image analysis and the roughness of particles measured with profilometer were also correlated with the micro-flotation experiments and aggregation analyses. The bubble-particle attachment time and fast-cam recordings were used to shed light on the possible mechanisms, i.e. roughness played a major role in its contribution of morphology on both flotation and aggregation of particles which were supported by fast-cam recordings as the larger bundle of particles and lower attachment time on bubble-particle attachment timer. In sum, adjusting the morphology of sulfide particles enhanced particle–particle interactions (aggregation) and led to improved bubble-particle interactions and in turn to flotation.